PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PADA NAIRA RESIDENCE PT KURNIA PUTRA SOEGAMA - Intan Lizzakiyah; Putri Nilam Kencana (Journal of Research and Publication Innovation, 2025)
The purpose of this research was to determine the effect of product quality and promotions simultaneously on purchasing decisions at Naira Residence PT. Kurnia Putra Soegama. The research method uses quantitative research methods. Based on the test results of Product Quality Variable on Purchase Decision with the regression equation Y = 5.540 + 0.680X1, the results of the correlation between Product Quality (X1) and Purchase Decision (Y) are 0.651 which is in the Correlation Coefficient Value Interval 0.600-0.799 meaning that it has a moderate relationship These results are in accordance with the criteria for the correlation coefficient table, and partially show that tcount is 6.593 > 1.66071, while t table is 1.66071 where tcount is greater than ttable or 6.593 > 1.66071 with a significance level of 0.000 1.66071 with a significance level of 0.038 > 0.05. Based on the results of simultaneous testing, the variable Product Quality and Promotion on Purchase Decision with the value of the regression equation: Y = 2.506 + 0.590X1 + 0.259X2 + 3.251e. The coefficient of determination (R square) is 0.449 or 44.9 while the remaining 55.1% is influenced by other factors, based on Fcount 18,761 with a significance of 0.000 with a significance level of 5% (0.05). Then the value obtained from Ftable 3.09 is obtained from df1 = 2 and df2 = 97 (2; 97). Because Fcount > Ftable (39.258 > 3.09 ) and the significance value (0.000<0,05) is smaller than the significance limit (0,05)